EFFECTIVENESS OF GOVERNMENT’S ELECTRONIC PROCUREMENT OF GOODS AND SERVICES IN ITS ROLE WITHIN THE GOVERNMENT’S PROJECTS - Yan Ari Wibowo; Trijeti Trijeti; Rachmad Irwanto (University Of Muhammadiyah Jakarta, 2022)
The government’s goods and services procurement are the major part in the state budget realization for its impact on performance of government’s departments. Considering the growing number of goods and services procurements, the government rules to set the procurement of goods and services electronically. This helps the government to run the state budget realization that is good in timekeeping, efficiency and accountability during procurement process. The effectiveness of electronic procurement of goods and services (e-procurement) of the government is strongly related to the government’s projects. This is presented in this study using a descriptive quantitative method on processed data output from SPSS v.23. The data was sourced from recorded government’s project in LKPP in 2019. The result shows good effectiveness level at 65,9% with supporting strong correlation value at 0,812 following consummated budget at 95,71%. Based on those statistics, this paper suggests that the run of government’s projects automatically would induce a consummated budget in which targets would be achieved and provide more benefits. Therefore, a good run of government’s projects needs better effectiveness of the government’s e-procurement of goods and services.